Indoor Radon Measurement in Dwellings of Khorramabad City, Iran - Hedieh Hassanvand; Mohammad Sadegh Hassanvand; Mehdi Birjandi; bahram kamarehie; ali jafari (Iranian Journal of Medical Physics, 2018)
Introduction: Exposure to indoor radon increases the risk of lung cancer. This study examined the level of indoor radon in dwellings of Khorramabad city, by using passive alpha-track detector (CR-39) during winter of 2016. Materials and Methods: In the present study, we detected the concentration of indoor radon in 56 dwellings. A passive sampling instrument (alpha-track detector with CR-39 polycarbonate films) was utilized to measure indoor radon gas concentration. The distribution map of indoor radon concentration was prepared using Arc GIS software. Results: Radon concentration in the dwellings varied from 1.08 to 196.78 Bq/m3, with a mean value of 43.43±40.37 Bq/m3. The average annual effective dose received by the residents of the studied area was estimated to be 1.09 mSv. Our results showed a significant difference between the average radon concentrations in houses and apartments, with a higher level in houses. Conclusion: Indoor radon concentration in 10.1% of the dwellings was determined to be higher than the limit (100 Bq/m3) recommended by the World Health Organization.